A study of meaning and purpose as a citizen among public university students in Malaysia - Adnan, Zatul Himmah; Ab. Razak, Ratna Roshida; Ku Samsu, Ku Hasnita; Lee, Yok Fee; Muhammad, Zarina; Marjuni, Alia Shuhada (Human Resource Management Academic Research Society, 2021)
A patriotic citizen is one of the qualities of a good citizen. To be patriotic, it requires the individual to understand the meaning and purpose of being a citizen and aware of moral and nationalistic duties for the country. There were some concerns about the purpose and meaning of youth as citizens of Malaysia when mass media and past studies often highlight the low spirit of patriotism among the youth in Malaysia. How they view their meaning and purpose as a citizen of Malaysia? This study aims to describe the meaning and purpose in life among public university students as citizens of Malaysia. The study was conducted among ten selected public university students in Malaysia through a descriptive quantitative methodology. The finding shows that the majority of the students have a high level of meaning and purpose in life. By having a positive virtues about life meaning and purpose, the study concludes that Malaysian university students have the quality of being good citizens.